Role of Social Media in Shaping Political Culture - Budhathoki, Bhup Bahadur (Journal of Rapti Babai Campus, 2025)
This article attempts to explore the influence of social media on building political culture at the international level, the role of major social media platforms, and the key stages where social media contributes to political culture formation. Based on a qualitative framework, the article utilizes purposive sampling methods to collect necessary information and statistics from various websites. With the onset of the 21st century and the expansion of the internet, the development and growth of various social media platforms have also surged. Social media has been playing a significant role in shaping global political culture and public opinion. Platforms like Facebook, Twitter, YouTube, WhatsApp, Instagram, WeChat, Reddit, and Telegram have brought millions of people together on a single stage, the factual details of which are presented in this article. Algorithms designed to enhance the effectiveness of social media play a vital role in political culture formation by repeatedly showing content based on people's preferences and thoughts. Similarly, boosting mechanisms for content have also contributed to building political opinions. Social media serves as a crucial tool for informing people about various programs and campaigns, increasing public participation, and effectively presenting demands to generate the necessary public opinion for their implementation by relevant authorities .Political culture formation involves specific stages where social media plays a supportive role. The article concludes that the expansion and rapid usage of social media in the present time have significantly influenced global politics. The number of social media platform users is increasing daily, and social media is playing a supportive role in the process of political culture and opinion formation.